Probing the surface structure via the adsorbed hydrogen atoms – The case of Cu(4 1 0) - Gueriba, Jessiel Siaron (Animo Repository, 2020)
We show how we could determine (or at least qualitatively deduce) the displacements of surface atoms with respect to an arbitrarily chosen reference, from the trends in the vibrational frequencies of adsorbed hydrogen atoms. The discernible displacement could be as small as 0.1 Å. As a test structure, we consider the case of Cu(4 1 0), which has remained contentious, until recently. Any slight (ca. 0.1 Å) displacement of Cu(4 1 0) surface atoms with respect to an arbitrarily chosen reference structure manifests as either a broadening or narrowing of the corresponding H-Cu(4 1 0) potential energy curve. This suggests the possibility of carry out adsorbate mediated surface analysis, with hydrogen as the (chosen) adsorbate, in this case. © 2020 Elsevier B.V.